2006
DOI: 10.1016/j.bbrc.2006.10.090
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the N-loop and β1-strand hydrophobic clusters of RANTES-derived peptides in anti-HIV activity

Abstract: HIV initiates its infectious cycle by docking to CD4 and a chemokine receptor, most commonly CCR5. RANTES, a natural CCR5 ligand, is a potent inhibitor of HIV-1. Despite the lack of structural information on the RANTES-CCR5 complex, determinants of HIV blockade were previously identified within the RANTES N-loop and β1-strand regions. A prototype N-loop/β1-strand peptide, named R11-29, contains two terminal hydrophobic stretches separated by a central hydrophilic region. Here, the role of the terminal hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The essential components for high potency were the C11-P18 segment found to be affected by Nt-CCR5 binding and the K25-Y29 segment [45] discovered in this study to be involved in ECL2 binding. F28A mutation was previously found by the same group to reduce the potency of a RANTES peptide by 80% [46]. These biological results are in agreement with our NMR results showing that K25 and F28 are involved in binding of RANTES to CCR5.…”
Section: Comparison With Gp120supporting
confidence: 93%
“…The essential components for high potency were the C11-P18 segment found to be affected by Nt-CCR5 binding and the K25-Y29 segment [45] discovered in this study to be involved in ECL2 binding. F28A mutation was previously found by the same group to reduce the potency of a RANTES peptide by 80% [46]. These biological results are in agreement with our NMR results showing that K25 and F28 are involved in binding of RANTES to CCR5.…”
Section: Comparison With Gp120supporting
confidence: 93%
“…Hence, it is mandatory to test new HIV-1 inhibitors for their ad- ditivity/synergy with existing drugs or other lead compounds. In this regard, the CCL5-derived peptide R4.0, the most active lead compound resulting from a long-lasting molecular evolution (10,(12)(13)(14), was subjected to an extensive combination survey. All compounds tested with their viral and cellular targets are illustrated in Fig.…”
Section: R4mentioning
confidence: 99%
“…In this context, a long-lasting project has been focused on the design of potent peptide-based HIV-1 entry inhibitors (12)(13)(14), with R4.0 as the most active representative (10). In view of its possible implementation in combination protocols, R4.0 was tested in various cellular assays for its compatibility with several HIV-1 inhibitors directed toward different viral/cellular targets.…”
mentioning
confidence: 99%
“…The prototypic peptide R11-29, derived from the natural sequence of the mature RANTES protein between aa 11 and 29, contains 2 clusters of hydrophobic residues (aa 11-16 from the N loop and aa 27-29 from the ␤1-strand) positioned at the 2 termini and connected by a 10-residue amphiphilic linker (aa [17][18][19][20][21][22][23][24][25][26]. We previously reported that the integrity of these 2 clusters is essential for the peptide biological activity (10). In the full-length chemokine, the 2 clusters are located at a distance of 13-14 Å from each other (C␣Ile15-C␣Tyr27) and contribute to the formation of a large solvent-exposed hydrophobic surface (11)(12)(13)(14).…”
Section: Stabilization Of the Hydrophobic N-terminal Region Of A Protmentioning
confidence: 99%
“…Using a combination of peptide scanning techniques, targeted mutagenesis, and structure-based modeling, we previously identified the main structural determinants of CCR5 binding and HIV-1 blockade within the N-loop and the ␤1-strand regions of RANTES (9,10). We found that synthetic peptides derived from these regions specifically 1 Correspondence: Laboratory of Immunoregulation, National Institute of Allergy and Infectious Diseases, National Institutes of Health, 10 Center Dr., Bethesda, MD 20892, USA.…”
mentioning
confidence: 99%